The Role of Marketplace in Building the Brand Trust on the Agricultural Products - Susan Purnama; Fitriani Reyta (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The agricultural sector is one of the potential sectors in Indonesia's economic growth. Business opportunities in the agricultural sector are currently in high demand. Technological advances are utilized in the e-commerce-based commerce system, namely the sale of agricultural products through online media known as the market place. In this research, the authors focus on how the market place influences consumer trust in agricultural product brands. The method used in this research is descriptive analytical about how the market place affects two indicators of brand trust, namely Brand Reliability and Brand Intention on agricultural product brands. The study population was taken as many as 150 online stores registered in one market place, and saturated samples were taken as much as 1 (one) online store in Bandung which is registered in one marketplace. The results showed that the market place had a significant influence on consumer confidence in agricultural product brands.